Perceived Internal Audit Roles and Challenges in a developing economy - Bananuka, Juma; Mukyala, Veronica; Nalukenge, Irene (Makerere Business Journal, 2017)
The purpose of this study was twofold: 1) to explore the perceived Internal Audit (IA) roles and challenges faced by internal auditors in fulfilling their mandate among listed firms in Uganda and 2) to examine the extent to which internal auditor challenges could inhibit the performance of internal auditor roles. Design/ methodology – This is an exploratory study with mixed methods design. We collected data from internal auditors of 13 listed firms in Uganda through both the questionnaire and interview guide. Data were analyzed using SPSS and XL STAT 2016 with Partial Least Square Modelling because of the small sample used in this study. Findings – We find eight (8) most perceived internal auditor roles in Uganda such as ‘internal audit reports on the system for generating financial information’. Many of these roles suggest that internal auditors perceive their roles consistent with traditional ones that were designed to safeguard firm’s assets and assist in the production of reliable accounting information for decision-making purposes. We also find five (5) most perceived internal auditor challenges such as ‘internal audit recommendations are not worked on by management’. Furthermore, these internal auditor challenges explain about 31% variation in perceived internal auditor roles. Research limitations/implications - As the internal auditors face many difficulties, it is difficult to see how they could perform their perceived roles effectively and thereafter embark on their expanded roles as espoused in the model charter of Institute of Internal Auditors (IIA). Although we employ a relatively small sample size, this study’s findings can be generalized to Uganda and other similar environments’ listed firms. The results are useful in informing the debates of the regulators, standard setters, external auditors, academicians and policy makers. If internal audit function appear incipient in listed firms in this environment, it could be a worthwhile endeavor to establish what it is like in non-listed firms. Originality / value – We examine perceived internal auditor roles, internal auditor challenges and how the latter affects the former using evidence from Uganda – a developing economy. We also contribute towards a methodological position of mixed methods design by producing results from a smaller sample augmented by interview results in an environment characterized by smaller populations so that inferences can be made. The interpretive research agenda caters to social aspects of internal auditing neglected by positivist studies that largely tackle questions founded in the realist ontological position.
Keywords: Internal auditor roles; Challenges; Uganda; Listed companies; Partial Least Square Modelling